2022
DOI: 10.3390/ijms23031438
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Oxidative Stress Biomarkers, Pro-Inflammatory Cytokines, and Histological Changes in Experimental Hypertension, Dyslipidemia, and Type 1 Diabetes Mellitus

Abstract: The present study aims to compare the oxidative stress biomarkers, pro-inflammatory cytokines, and histological changes induced by three cardiovascular risk factors, namely, hypertension, dyslipidemia, and type 1 diabetes mellitus. Hypertension was induced with 40 mg/kg body weight (b.w.) of N omega-nitro-L-arginine-methyl (L-NAME) administered orally. Dyslipidemia was induced by the administration of a diet with a high cholesterol (2%) content. Diabetes mellitus was induced by intraperitoneal administration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…Recent novel findings by Boarescu and colleagues (2022) showed the importance of prevalent cardiovascular risk factors with MDA. Hypertension, lipid imbalance, and diabetes mellitus were associated with a slight increase in the concentration of MDA [ 42 ]. Similarly, Charkiewicz and colleagues (2021) demonstrated the increase of MDA in male subjects with hypertension.…”
Section: Oxidant Biomarkers In the Diagnosis And Prognosis Of Cvdmentioning
confidence: 99%
“…Recent novel findings by Boarescu and colleagues (2022) showed the importance of prevalent cardiovascular risk factors with MDA. Hypertension, lipid imbalance, and diabetes mellitus were associated with a slight increase in the concentration of MDA [ 42 ]. Similarly, Charkiewicz and colleagues (2021) demonstrated the increase of MDA in male subjects with hypertension.…”
Section: Oxidant Biomarkers In the Diagnosis And Prognosis Of Cvdmentioning
confidence: 99%
“…Similarly, an animal experimental study that included a total of 28 Wistar-Bratislava white male rats showed that dyslipidemia, hypertension, and diabetes mellitus were associated with an increase in serum MDA levels (37). Another experimental study (38) showed that isolated adipocytes from adipose tissue from mice fed on a diet enriched with fat were characterized by insulin resistance and a twofold increase in the production of ROS which led to metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Total oxidant status (TOS) is another pro-oxidant marker often used to estimate the overall oxidation state of the body [ 68 ], while TAC is an antioxidant marker used to evaluate the antioxidant capacity of the body [ 69 ]. It was already observed that diclofenac administration reduces TOS and increases TAC in carrageenan-induced paw edema inflammation in rats [ 70 ].…”
Section: Discussionmentioning
confidence: 99%